2014
DOI: 10.2752/175303714x14023922797904
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Exhibits May be More Effective Than Traditional Exhibits at Improving Zoo-Visitor Attitudes toward African Apes

Abstract: Zoos play a unique role in wildlife conservation, particularly in the area of conservation education. Because of their popularity and flagship status for broader conservation issues, great apes may prove to be one of the most important educational conduits in zoos. In 2002, we surveyed knowledge of and attitudes toward African apes in visitors to the Lester E. Fisher Great Ape House (GAH) at Lincoln Park Zoo in Chicago, IL, USA. In the current study, we replicated the survey to document attitudes to and knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
0
24
0
1
Order By: Relevance
“…However, if the direct experience offered by this immersion exhibit led to an increase in connectedness to nature, it follows that immersion exhibits and experiences may also lead to an increase in positive attitudes and positive emotions. Lukas and Ross (2014) did find that naturalistic zoo exhibits were more likely to lead to attitude change than traditional zoo exhibits. Likewise, the study also used a purposive sample of visitors that self-selected to see the exhibit.…”
Section: Resultsmentioning
confidence: 89%
“…However, if the direct experience offered by this immersion exhibit led to an increase in connectedness to nature, it follows that immersion exhibits and experiences may also lead to an increase in positive attitudes and positive emotions. Lukas and Ross (2014) did find that naturalistic zoo exhibits were more likely to lead to attitude change than traditional zoo exhibits. Likewise, the study also used a purposive sample of visitors that self-selected to see the exhibit.…”
Section: Resultsmentioning
confidence: 89%
“…The questionnaire was developed using many of the same questions and statements to evaluate knowledge of and attitudes toward African apes of visitors to a former and renovated ape exhibit at Lincoln Park Zoo in Chicago, IL (Lukas & Ross, , ). Each survey took approximately 10 min to complete.…”
Section: Methodsmentioning
confidence: 99%
“…Our closest relatives, the great apes, are one of the most popular animals in zoos and education programs are commonly based on these mega‐charismatic animals (Stoinski, Ogden, Gold, & Maple, ). For example, evaluation surveys have demonstrated that watching great apes at exhibits and providing relevant information about their natural history and conservation helps to increase knowledge among exhibit visitors and strongly suggest improved pro‐great ape attitudes (Lukas & Ross, , ). The degree to which knowledge increase happens depends on education levels and age, whereas better attitudes toward great apes were prevalent among younger people (ibid).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studied variables include naturalness and interactiveness of the exhibits (e.g. Swanagan 2000; Ballantyne et al 2007, 372;Ross et al 2012;Lukas & Ross 2014), animal activity and eye contact with the animals (Powell & Bullock 2014), animal charisma (Smith & Sutton 2008), interpretation of conservation (by guides) (Jacobs & Harms 2014) or duration of stay (Smith & Broad 2008). The post-visit material has also proved important (e.g.…”
Section: Introductionmentioning
confidence: 99%